Is Agar biased against ‘post-persons’? - Persson, Ingmar (Journal of medical ethics, 2013)
I shall discuss only one of Nicholas Agar's main claims,1 namely ‘that the bad consequences/of moral status enhancement/are, in moral terms, so bad that a moderate probability of their occurrence makes it wrong not to seek to prevent them’. His other main claim, which I grant, is that moral status enhancement to the effect of creating beings with a moral status higher than that of (mere) persons—post-persons—is possible. My chief objection to Agar's argument is that it is biased in favour of (mere) persons. This comes out when he sums it up: ‘the creation of post-persons would be a morally bad thing. It is likely to impose significant penalties on mere persons’. Suppose it is true that the creation of post-persons will impose such significant penalties on mere persons that they are worse off than they were before the creation of post-persons. Then it follows that the creation of post-persons is bad for mere persons, but it does not follow that it is bad overall. This follows only if it is not the case that post-persons receive benefits to an extent that morally outweighs the burdens to mere persons. (For simplicity, I bracket sentient non-persons.) As far as I can see, Agar does not show this—that is why I think he is biased towards mere persons, and simply assumes that what is bad for them is bad overall. I have, in fact, been too concessive to Agar …